Evaluation and Prioritization of Service Quality Dimensions Using Dematel and Topsis (A Case Study in Iran) - Khanjankhani, Khatere; Rafiei, Sima; Ezzatabadi, Mohammad Ranjbar; Askari, Roohollah; Abooee, Fatemeh; Shafii, Milad (BALI MEDICAL JOURNAL, 2016)
Background: Hospital services quality plays an increasingly important role in today’s competitive environment. This study aimed to evaluate causal effects of different healthcare quality aspects on quality of services perceived by patients in hospitals affiliated by Shahid Sadoughi University of Medical Sciences using DEMATEL and TOPSIS techniques in 2014. Method: Through literature review and expert opinions, different service quality dimensions in under study hospitals were identified and required data were gathered. In the next step, DEMATEL technique was applied to determine cause and effect relationships between identified quality aspects and quality perceived by service recipients. Also to rank dimensions according to their priorities, TOPSIS method was used. Given the literature review, six quality dimensions including responsiveness, assurance, security, tangibility, communication and patient centeredness were identified. Result: Results obtained from DEMATEL technique introduced patient security as an influential aspect which was ranked in the sixth place in terms of importance. Conclusion: The prioritization of quality dimensions along with their causal effects provides a beneficial insight for hospital managers to effectively plan and make improvement decisions. It is suggested that considering a remarkable impact of security on patients’ perception toward quality of care, this aspect should be regarded in decision makers’ programs with a greater emphasis.